PENDEKATAN PERANCANGAN ARSITEKTUR NEO-VERNAKULAR DI KAWANGKOAN TERMINAL BUS TIPE B - Duma, Yafet; Katuuk, Antoinette L. Grace; Liando, Cindy M. (Jurnal Ilmiah Desain Sains Arsitektur (DeSciArs), 2025)
This design aims to design a Type B Bus Terminal to meet and complement the needs of passengers in Kawangkoan, Minahasa Regency, North Sulawesi. Site area 31,067 m2, KDB 40% = 12,427 m2, KDH 60% = 15,545 m2. According to BPS Minahasa in 2017-2022, the number of people in Minahasa is increasing, with this increase, more and more people need vehicles from one place to another, the author conducted a survey in the Kawangkoan area which only has one terminal and a terminal that is only 1ha in size, does not have adequate availability of transportation facilities and infrastructure such as irregular vehicle circulation that is not yet available signs and directions so that it has not met the standards of Terminal Type B. The steps in this design process include Data Collection, Analysis and Synthesis / Concept, so that in this design can be realized properly and meet Type B Terminal Standards.